PROFESSIONALISM IN TEACHING ENGLISH FOR YOUNG LEARNER - Luluk Aulia Aghni (Universitas Indo Global Mandiri, 2022)
Professionalism is an important thing that every people should have if they want to succeed and move ahead. In teaching world, professionalism is also important. Professionalism in teaching means the professional teachers who have been qualified where they can face the difficulties in teaching by the skills and experiences they have. Teaching English for young learners is not as easy as what people think, the teachers of young learners must be aware of children’s basic physical and psychological needs, they should provide the care necessary to meet the needs so they can thrive and focus in learning. Most of English teachers of primary school are graduated from the primary school teacher education (PSTE) where they have enough skill in teaching young learners but they do not have enough knowledge English. This problem can caused the students get lost if the teachers are not properly skilled and professional.